Using parent newsletters to enhance junior primary school mathematics : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Studies (Mathematics) at Massey University - Savell, Janice Robyn (Massey University, 1998)
Parent Newsletters were investigated as a means of increasing home-school contact in the Junior Primary School mathematics classroom. An action research model using three cycles, was used to develop and trial the newsletter. The first newsletter was based on BSM activities and used by five teachers at a school sited in a military housing area. The second and third formats of the newsletters were written in consultation with one teacher to integrate with her topic based mathematics programme in a Palmerston North primary school. A questionnaire was used to gather background information and invite parents to be interviewed for further comments. Teachers and responding parents were interviewed in a semi-structured format. Participants commented on a range of other home-school contact issues. A follow-up interview was conducted with the parents from the Palmerston North school three months after the newsletters had ceased. Teachers and parents were positive about the benefits of the newsletters. Newsletters did increase parental awareness of the junior school mathematics programme. For one child with special needs an obvious improvement in classroom performance was directly attributable to the effect of the newsletters. Interviews revealed a number of inconsistencies between parents and teacher views of their roles and responsibilities. Problems of parent-school communication were highlighted. Teachers supported the newsletters, but felt that heavy workloads did not allow time for teacher production. The research tentatively confirms the value of mathematics newsletters as a means of helping children and as a means of keeping parents informed. additionally, the research gives rise to questions on the duality of information flow and equality of benefits accrued.
Keywords: New Zealand; Home and school; Parent-teacher relationships; Mathematics; Education; Parent participation; Study and teaching